Predictors of health seeking behavior for fever cases among caregivers of under-five children in malaria-endemic area of Imo State, Nigeria - Oluchi, Sampson Emilia; Abdul Manaf, Rosliza; Ismail, Suriani; Udeani, Theophilus Kachidelu (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
Fever is one of the most common symptoms of pediatric illnesses; it is an important early symptom of malaria. Fever had served as the entry point for presumptive treatment of malaria among children in Nigerian. Appropriate HSB is important when seeking treatment for fever among under-five children; this will help for better prognosis because treatment will be initiated early. This study attempted to identify caregiver’s HSB for under-five children with fever. A cross-sectional study was conducted in Imo-State, Nigeria. Appropriate HSB was operationally defined as seeking treatment from health facility within 24h of fever. Data were obtained using pretested self-administered questionnaire. Data were analyzed using SPSS version 22. Simple and multiple logistic regression were used to determine predictors of appropriate HSB. A total of 559 eligible respondents were recruited; 103 (18.6%) caregivers had appropriate HSB. The predictors of HSB are being male child (aOR = 2.760; 95% CI:1.536–4.958), the age of child younger than 27 months (aOR = 2.804; 95% CI:1.485–5.295), employed caregivers (aOR = 1.882; 95% CI:1.014–3.493), number of household members (aOR = 2.504; 95% CI:1.464–4.283), and caregivers who decided to seek treatment at early stage (aOR = 7.060; 95% CI:1.616–30.852). Only 18.6% caregivers practiced appropriate HSB for fever cases among under-five children. It is essential to educate caregivers and emphasise on early treatment of fever and appropriate use of health facilities for fever. The findings will be used to improve intervention at the community level and will be compared with follow-up data to evaluate their effectiveness.